Evaluation of Flow Rate, pH, Buffering Capacity, Calcium, Total Protein and Total Antioxidant Levels of Saliva in Caries Free and Caries Active Children—An In Vivo Study - Prabhakar, AR (Jaypee Brothers Medical Publishers, 2009)
Background and objectives: The purpose of this study was to evaluate the relationship between the physicochemical properties of saliva such as flow rate, pH, buffering capacity, calcium level, total protein and total antioxidant levels in caries free and caries active children. Materials and methods: The present study included one hundred and twenty healthy children who were divided into two groups and subdivided according to gender. They were further divided into caries free and caries active children with 15 children in each group. Unstimulated saliva was collected by suction method and flow rates were determined. The samples were then analyzed for pH, buffering capacity, total protein, calcium and total antioxidant levels. The data was then statistically analyzed using student’s ‘t’ test {unpaired}. Results: The results revealed that when all these parameters were compared among the caries free and caries active children, the flow rate, pH and buffering capacity were slightly reduced in caries active children, but the total protein and total antioxidant capacity of saliva increased significantly in caries active children and the total calcium decreased significantly in caries active children. Conclusion: Within the limitation of this study, we can conclude that, the physicochemical properties of saliva play a major role in the development of caries.